2021
DOI: 10.3390/en14164905
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Natural Gas Consumption Forecasting Based on Analog Method and Fuzzy Decision Tree

Abstract: Classic forecasting methods of natural gas consumption extrapolate trends from the past to subsequent periods of time. The paper presents a different approach that uses analogues to create long-term forecasts of the annual natural gas consumption. The energy intensity (energy consumption per dollar of Gross Domestic Product—GDP) and gas share in energy mix in some countries, usually more developed, are the starting point for forecasts of other countries in the later period. The novelty of the approach arises i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Traditional time series models are often replaced by artificial neural networks, including deep neural networks and long short-term memory (LSTM) [29][30][31]. Long-term forecasting is the research area in only about 20% of studies [10,16,17,32]. Usually, long-term forecasts are constructed using models with dependent macroeconomic variables (GDP, population, unemployment rate, etc.…”
Section: Natural Gas Forecasting Researchmentioning
confidence: 99%
“…Traditional time series models are often replaced by artificial neural networks, including deep neural networks and long short-term memory (LSTM) [29][30][31]. Long-term forecasting is the research area in only about 20% of studies [10,16,17,32]. Usually, long-term forecasts are constructed using models with dependent macroeconomic variables (GDP, population, unemployment rate, etc.…”
Section: Natural Gas Forecasting Researchmentioning
confidence: 99%
“…These disruptions have worsened the difficulty of alternative last-mile options in urban logistics, resulting in novel package delivery systems that mix physical and digital solutions such as self-collection delivery systems. Self-collection delivery systems benefit both courier companies and clients by providing time-window flexibility while lowering overall mileage, delivery time, and, as a result, gas emissions [94,95].…”
Section: Graph Representations Of Automated Smart Locker System Optim...mentioning
confidence: 99%
“…Using cluster mathematical analysis (i.e., analogue methods and fuzzy decision trees), ref. [16] drew attention to an innovative approach to long-term forecasting of natural gas consumption at the level of 79 countries in the period 1960-2019. Based on the macroeconomic variables used (GDP, GDP per capita, population, value added of industry to total GDP, CO 2 emissions, energy intensity of GDP, share of natural gas consumption in the energy mix, HDD index, and annual natural gas consumption), it was found that the model leads to better results, in terms of increased performance and level of accuracy, in the analysis of forecasting annual natural gas consumption and production per capita.…”
Section: Theoretical Backgroundmentioning
confidence: 99%